Seroprevalence of cytomegalovirus infection in pregnant woman of socioeconomically advantaged class from brazil - Serra, Fabiana C.; Machado, Janaina; Nicola, Maria Helena; Jorge, Maria Claudia A. Silva; Cruz, Luiz Eduardo da; Giordano, Mario Vicente; Silva, Ricardo O. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: congenital cytomegalovirus is the most common intrauterine infection in the world, causing central nervous malformation, deafness and poor acquaintance of knowledge. Notwithstanding, few studies are addressed studying this infection in Brazilian and Latin America pregnat women. Objective: the aim of this study was to establish the seroprevalence of cytomegalovirus in advantaged socioeconomic class pregnants in Brazil. Methods: we search the seroprevalence of cytomegalovirus in high socioeconomic pregnant women in Brazil and the profile of the infection in our country. Our study was observational/transversal, with pregnant women attended at Cryopraxis Criobiology Ltda. Blood from umbilical cord was collected from January 2005 until December 2006 with analyzing IgM and IgG antibodies for cytomegalovirus (immunoassay and chemiluminescence). Results: we obtained 4,620 samples, 1966 (42%) from Rio de Janeiro, 1,695 (37%) from São Paulo State and 959 (21%) from other states. 3894 (84%) were IgG positivity to cytomegalovirus, with high prevalence. Only 64 (1,4%) of the pregnants were suggestively acute infection (IgM positive). Conclusion: although cytomegalovirus infection is frequently associated with lower socioeconomic class, the seropositivity of IgG is high in pregnant women of high socioeconomic class in Brazil. In many cases, previous contact with viruses was not evident, which warns about the maternal susceptibility to infection and consequent risk of fetal transmission in this population. There is no specific treatment of the disease. Then, serology is important for adequate attendance, reducing the risk of congenital infection.